Oberlin, Hotbed of Abolitionism : College, Community, and the Fight for Freedom and Equality in Antebellum America - Morris, J. Brent (Book collections on Project MUSE., 2014)
Oberlin, Hotbed of Abolitionism: College, Community, and the Fight for Freedom and Equality in Antebellum America.